NEW INSIGHTS ON LONG DISTANCE FAULT INTERACTION - Melini D.; Casarotti E.; Piersanti A.; Boschi E. (My University, 2002)
We investigated the plausibility of remote fault triggering on a global scale as a result of postseismic stress transfer by large earthquakes. Previous studies have shown that the postseismic stress field generated by eight of the largest events that have occurred in the Pacific area promoted the rupture of 53.6% of all the M=<5 events recorded in the last century in the circumpacific ring. We tried to assess the statistical significance of this result by performing a set of new statistical simulations involving very intensive computational tasks. To this aim we implemented a new numerical procedure based on parallel codes. We found that our simulations did not show strong statistical evidence, but there was a clear indication that as we applied more realistic geometrical constraints to the synthetic distributions, we tended to reproduce more closely the observed quantities. These results support the hypothesis of some kind of physical connection of the configuration of a plate margin and its activity with those of all the other plate margins, more than the possibility of remote fault interaction in the 'classical' sense.
Keywords: POSTSEISMIC STRESS; VISCOELASTIC RELAXATION; FAULT INTERACTION; GLOBAL SCALE; SYNTHETIC CATALOGUES; SUPERCOMPUTING APPLICATION